Peptide chemistry and drug design - Dunn, Ben M. (Hoboken, New Jersey : Wiley, 2015)
'This book details many of the problems and successes of peptides as potential drugs'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Peptides -- chemistry; Drug Design; Pharmaceutical preparations